Identification of a Recessive Gene PmQ Conferring Resistance to Powdery Mildew in Wheat Landrace Qingxinmai Using BSR-Seq Analysis - Li, Yahui (Plant disease, 2020)
Wheat powdery mildew is caused by Blumeria graminis f. sp. tritici (Bgt), a biotrophic fungal species. It is very important to mine new powdery mildew (Pm) resistance genes for developing resistant wheat cultivars to reduce the deleterious effects of the disease. This study was carried out to characterize the Pm gene in Qingxinmai, a winter wheat landrace from Xinjiang, China. Qingxinmai is resistant to many Bgt isolates collected from different wheat fields in China. F1, F2, and F2:3 generations of the cross between Qingxinmai and powdery mildew susceptible line 041133 were developed. It was confirmed that a single recessive gene, PmQ, conferred the seedling resistance to a Bgt isolate in Qingxinmai. Bulked segregant analysis-RNA-Seq (BSR-Seq) was performed on the bulked homozygous resistant and susceptible F2:3 families, which detected 57 single nucleotide polymorphism (SNP) variants that were enriched in a 40 Mb genomic interval on chromosome arm 2BL. Based on the flanking sequences of the candidate SNPs extracted from the Chinese Spring reference genome, 485 simple sequence repeat (SSR) markers were designed. Six polymorphic SSR markers, together with nine markers that were anchored on chromosome arm 2BL, were used to construct a genetic linkage map for PmQ. This gene was placed in a 1.4 cM genetic interval between markers Xicsq405 and WGGBH913 corresponding to 4.9 Mb physical region in the Chinese Spring reference genome. PmQ differed from most of the other Pm genes identified on chromosome arm 2BL based on its position and/or origin. However, this gene and Pm63 from an Iranian common wheat landrace were located in a similar genomic region, so they may be allelic